UPAYA PENINGKATAN KEMAMPUAN GURU SEKOLAH DASAR DALAM PEMBELAJARAN BERPUSAT KOOPERATIF MELALUI SUPERVISI KLINIS DI SD NEGERI 02 KARAN AUR KOTA PARIAMAN TAHUN 2020 - Huda, Nurul (Ensiklopedia Education Review, 2020)
The objectives of this school action research are; To find out the ability of elementary school teachers with a cooperative learning model through clinical supervision at SD Negeri 02 Karan Aur, Kota Pariaman. The research subjects were 8 teachers of SD Negeri 02 Karan Aur. The results of the analysis that has been carried out using clinical supervision in improving the ability of teachers to use cooperative models are very good. At the beginning of the activity the teacher was still hesitant to use this model, but because of the guidance of researchers through clinical supervision, the teacher was able to use the cooperative model. 87% of teachers are able to use cooperative models in the learning process and this also affects the potential of students.